Application of FeCl3/Diorganyl Diselenides to Cyclization of o-Alkynyl Anilines: Synthesis of 3-Organoselenyl-(N-methyl)indoles - Sperança, Adriane; Godoi, Benhur; Menezes, Paulo Henrique; Zeni, Gilson (Synlett, 2013)
In this manuscript we described the FeCl3/diorganyl diselenides promoted intramolecular cyclization of o-alkynyl anilines, as an alternative for the construction of functionalized 3-organoselenyl indoles. The cyclization reactions proceeded smoothly at room temperature in the presence of air giving the 3-organoselenyl indoles in good yields. Additionally, the 3-organoselenyl indoles proved to be quite useful as synthetic intermediates for the construction of more functionalized indole units through a selenium–lithium exchange reaction followed by trapping the lithium intermediate with different electrophiles.
Keywords: indole; iron salt; cyclization; selenium